2014
DOI: 10.1260/2040-2295.5.3.329
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Medical Equipment Management in Relation to the Mandatory Medical Equipment Safety Manager (MESM) in Japan

Abstract: Half a decade has passed since the fifth revision of the medical law and mandatory appointment of a medical equipment safety manager (MESM) in hospitals in Japan. During this period, circumstances have changed regarding maintenance of medical equipment (ME). We conducted a survey to examine these changes and the current situation in ME management. Maintenance of ME and related work were found to have increased in many hospitals, but the number of clinical engineering technologists (CETs) has only slightly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Based on some interviews, it is concluded that maintenance management in the public hospitals was not effective. The same conclusion was reported by Ishida et al (2014), who conducted a survey to examine these changes and the current situation of maintenance management in Japan public healthcare. AbdRania et al (2015) looked into the relationship between maintenance strategies implemented in healthcare facilities in Malaysia.…”
Section: Empirical Studies: Maintenance Performance Measurement (Mpm)supporting
confidence: 70%
“…Based on some interviews, it is concluded that maintenance management in the public hospitals was not effective. The same conclusion was reported by Ishida et al (2014), who conducted a survey to examine these changes and the current situation of maintenance management in Japan public healthcare. AbdRania et al (2015) looked into the relationship between maintenance strategies implemented in healthcare facilities in Malaysia.…”
Section: Empirical Studies: Maintenance Performance Measurement (Mpm)supporting
confidence: 70%
“…Medical equipment use safety management is a complex MS that consists of medical equipment, the medical environment (software and hardware), users, and clinical medical engineers [18][19][20]. The information system based on the chain process improves the efficiency of cooperation among different departments.…”
Section: Discussionmentioning
confidence: 99%
“…12. (3) Improving management Fig. 12 The flow of equipment purchasing The management of medical equipment puts forward higher requirements for managers [18]. Hospitals should regularly train and evaluate equipment management staffs, strive to improve the management level of managers, and encourage office staffs to manage equipment and reduce equipment loss caused by human factors and give full play to the value of equipment through proper reward and punishment mechanism.…”
Section: Discussionmentioning
confidence: 99%